Atividade antinociceptiva e antioxidante do derivado tiofênico 2-amino-4,5,6,7-tetrahidro-benzotiofeno-3-carbonitrila (6CN) em camundongos - Penha, Antônia Rosângela Soares (2014)
Of heterocyclic compounds, thiophenols stand out due to their potential as a prototype for the development of new drugs, are known to exhibit various biological activities. The thiophenic derivative 2-amino-4 ,5,6,7-tetrahydro-benzothiophene-3-carbonitrile (6CN) is synthesized by reacting Gewald. This study aimed to investigate the antinociceptive and antioxidant activity of the thiophenic derivative 2 - amino - 4,5,6,7 - tetrahydro - benzothiophene - 3 - carbonitrile (6CN) in Swiss mice. Initially, the LD50 (lethal dose 50 %) of 6CN, the result was 557.5 mg/kg. All different doses tested in pharmacological screening tests, induced to psicodepressant behavioral changes such as reduced ambulation and decreased response to touch and analgesia. Then tests were performed to evaluate the muscle relaxant, sedative and anxiolytic activity. The 6CN presented relaxant and sedative activity at doses of 50 and 100 mg/kg in the rotarod and the thiopental sleep induction test, respectively, and anxiolytic activity at doses of 25 and 50 mg/kg in the test plus maze. The antinociceptive activity was tested using the writhing induced by acetic acid, formalin and hot plate tests. The 6CN increased the latency to the onset of writhing induced by acetic acid and reduced the number of writhes when compared to the control group at doses of 25, 50 and 100 mg/kg. In the formalin test, 6CN 100 mg/kg dose reduced the time of paw licking in the neurogenic phase (0-5 min). The licking time reduced at all doses tested during the subsequent inflammatory phase (15-30 min). In the hot plate test, 6CN increased the latency time at doses of 50 and 100 mg/kg in the first 30 min. Using 6CN 100 mg/kg dose the effect lasted during all the experiment. The study used the opioid, adenosinergic, dopaminergic, muscarinic, L-arginine-nitric oxide, GABAergic and sensitive K + channels to ATP (K+ATP) pathways as pharmacological tools to elucidate the antinociceptive action of 6CN. Caffein reversed the antinociception produced by 6CN in the neurogenic and inflammatory phase of the formalin test. Whereas haloperidol reversed only the second phase of the formalin test, suggesting the involvement of adenosine and dopamine receptors. The 6CN showed antioxidant activity, evaluated by testing the scavenging activity of DPPH and trolox equivalent antioxidant capacity (CAET), with EC50 values of 4.7 and 1.1 g/ml, respectively. Therefore, this study demonstrated that the 6CN has anxiolytic, antinociceptive activity , with participation of adenosinergic and dopaminergic systems. It also has antioxidant activity for DPPH and ABTS radicals.